Identification of methylated genes in salivary gland adenoid cystic carcinoma xenografts using global demethylation and methylation microarray screening - LING, SHIZHANG (Int J Oncol, 2016)
Salivary gland adenoid cystic carcinoma (ACC) is a rare head and neck malignancy without molecular biomarkers that can be used to predict the chemotherapeutic response or prognosis of ACC. The regulation of gene expression of oncogenes and tumor suppressor genes (TSGs) through DNA promoter methylation may play a role in the carcinogenesis of ACC. To identify differentially methylated genes in ACC, a global demethylating agent, 5-aza-2′-deoxycytidine (5-AZA) was utilized to unmask putative TSG silencing in ACC xenograft models in mice. Fresh xenografts were passaged, implanted in triplicate in mice that were treated with 5-AZA daily for 28 days. These xenografts were then evaluated for genome-wide DNA methylation patterns using the Illumina Infinium HumanMethylation27 BeadChip array. Validation of the 32 candidate genes was performed by bisulfite sequencing (BS-seq) in a separate cohort of 6 ACC primary tumors and 6 normal control salivary gland tissues. Hypermethylation was identified in the HCN2 gene promoter in all 6 control tissues, but hypomethylation was found in all 6 ACC tumor tissues. Quantitative validation of HCN2 promoter methylation level in the region detected by BS-seq was performed in a larger cohort of primary tumors (n=32) confirming significant HCN2 hypomethylation in ACCs compared with normal samples (n=10; P=0.04). HCN2 immunohistochemical staining was performed on an ACC tissue microarray. HCN2 staining intensity and H-score, but not percentage of the positively stained cells, were significantly stronger in normal tissues than those of ACC tissues. With our novel screening and sequencing methods, we identified several gene candidates that were methylated. The most significant of these genes, HCN2, was actually hypomethylated in tumors. However, promoter methylation status does not appear to be a major determinant of HCN2 expression in normal and ACC tissues. HCN2 hypomethylation is a biomarker of ACC and may play an important role in the carcinogenesis of ACC.